2018
DOI: 10.1177/1046496418785019
|View full text |Cite
|
Sign up to set email alerts
|

Language and Group Processes: An Integrative, Interdisciplinary Review

Abstract: This article reviews research that examines the use of language in small interacting groups and teams. We propose a model of group inputs (e.g., status), processes and emergent states (e.g., cohesion, influence, and innovation), and outputs (e.g., group effectiveness and member well-being) to help structure our review. The model is integrated with how language is used by groups to both reflect group inputs but also to examine how language interacts with inputs to affect group processes and create emergent stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 125 publications
(243 reference statements)
2
66
0
Order By: Relevance
“…This approach will enable us to examine turn transitioning in cancer MDMs, while focusing on how language affects group interaction. This is important because the literature shows that the way language is used can affect their inputs, processes and outputs (Van Swol & Kane, 2019). Language can also determine the successful implementation of interventions and therapies for patients (Jordan et al, 2009).…”
Section: Methodologies For Studying Turn-takingmentioning
confidence: 99%
“…This approach will enable us to examine turn transitioning in cancer MDMs, while focusing on how language affects group interaction. This is important because the literature shows that the way language is used can affect their inputs, processes and outputs (Van Swol & Kane, 2019). Language can also determine the successful implementation of interventions and therapies for patients (Jordan et al, 2009).…”
Section: Methodologies For Studying Turn-takingmentioning
confidence: 99%
“…Third, the proposed dictionaries and LIWC software enable analyses of large quantities of data, where manual coding would be highly time-consuming (Neuendorf, 2011;Rudy, Popova, & Linz, 2010). Recently, text analysis started to play a significant role in psychological research (e.g., Eichstaedt et al, 2015;Gustafsson Send en et al, 2014;Mooijman, Hoover, Lin, Ji, & Dehghani, 2018;Van Swol & Kane, 2018), for instance, in reliably evaluating an individual's personality, status, or mood just based on the use of pronouns (see Campbell & Pennebaker, 2003;Pennebaker, 2011). Thus, analyzing 400,000 articles (a dataset released by Reuters for research and the development of natural language processing) would take 400,000 hours, which would require 200 full-time coders working for a year if every article were analyzed for an hour (based on 2,000 working hours per year; for details see Gustafsson Send en, Sikstr€ om, & Lindholm, 2015).…”
Section: Future Researchmentioning
confidence: 99%
“…Prior research indicates that people with a self-focus tend to use more I pronouns and people with an other-focus tend to use more we pronouns (Van Swol & Kane, 2019), and advice recipients with an other-focus are more likely to implement advice (Duan et al, forthcoming). On this basis, we proposed that the use of I pronouns would be negatively related to implementation intention, and the use of we pronouns positively related.…”
Section: Discussionmentioning
confidence: 99%
“…Use of I pronouns reflects a self-focus, whereas use of we pronouns is indicative of other-focus. For example, research has found that group members with a more collective focus use more we pronouns, whereas members who are more focused on themselves use more I pronouns (Van Swol & Kane, 2019). Given the relationship between other-focus and advice utilization, advice recipients who use more I pronouns to describe their problems should have lower intention to implement advice, whereas those who use more we pronouns should have higher intention to implement advice.…”
Section: Recipient Behaviors That Impact Recipient Response To Imposementioning
confidence: 99%